THE PERSISTENCE PARADOX: A SELF-DETERMINANT THEORY (SDT) ANALYSIS OF PSYCHOLOGICAL RESILIENCE AND MOTIVATIONAL VULNERABILITY IN TVET STUDENTS (PRELIMINARY DESCRIPTIVE ANALYSIS) - Godfrey, Meta Melanie P.; Malek, Mohd Dahlan Hj. A.; Juli, Elpidia (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This quantitative descriptive study, guided by Self-Determination Theory (SDT), analyzed the motivational profile and psychological vulnerability of underprivileged students (N=85) enrolled in a Technical and Vocational Education and Training (TVET) program. This research was initiated to provide the necessary empirical foundation for a broader study on student resilience, following a problem statement revision to focus on soft skills issues. The study empirically examined the "Persistence Paradox": the co-existence of high sustained effort with a statistically low foundation of autonomous motivation. Data from the Student Cognitive and Academic Questionnaire (SCAQ) underwent reliability and descriptive analysis. The instrument demonstrated strong internal consistency across 47 items (Cronbach Alpha = 0.773). Descriptive results confirmed a critical motivational imbalance: high Controlled Extrinsic Motivation ("Getting a vocational certificate is very important for me," Mean = 8.41) was significantly contrasted by low Intrinsic Motivation ("I am enjoying my academic work at Montfort," Mean = 4.31). Furthermore, the high reported mean for "trouble concentrating" (Mean = 6.60) signals a pervasive frustration of the Basic Psychological Needs (BPNs) for Autonomy and Competence. The findings characterize student resilience as potentially fragile due to its controlled motivational source, providing a strong quantitative basis for the planned follow-up qualitative investigation.